Higher wages or lower expectations? Adjustments of German firms in the hiring process - Hanna Brenzel; Anne Müller (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2015)
Labour shortages are a field of research that has been investigated quite thoroughly. The reactions of firms facing problems during the hiring process are, however, largely neglected in empirical literature. Our research will fill this empirical gap and shed light on the question of whether reactions according to the neoclassical theory or to the Reder Hypothesis are more common in reality. We make use of a unique dataset, the German Job Vacancy Survey, which allows us to observe the entire operational recruitment process including potential problems, concessions made by firms as well as characteristics of the hired candidate, the vacancy and the firm itself. Whether concessions are made mainly depends on the labour market situation and on the specific hiring problems of a firm. We also find that firms are rather flexible in their reactions in accordance with the specific hiring problem. Therefore, both theories seem to apply in reality. – – Das Thema Arbeitskräfteengpässe wurde bereits umfangreich erforscht, allerdings blieben dabei die Reaktionen von Betrieben mit Schwierigkeiten im Einstellungsprozess weitestgehend unberücksichtigt. Unsere Forschung soll diese Lücke schließen und Aufschluss darüber geben, ob auf dem deutschen Arbeitsmarkt eher die neoklassische Theorie oder aber die Reder-Hypothese Anwendung findet. Für unsere Analysen greifen wir auf die IAB-Stellenerhebung zurück. Dieser Datensatz ermöglicht es den gesamten Rekrutierungsprozess zu beobachten, einschließlich der Probleme die dabei auftreten können, mögliche Zugeständnisse seitens der Unternehmen als auch personen-, stellen- und firmenspezifische Charakteristika. Ob Zugeständnisse gemacht werden hängt vor allem von der Arbeitsmarktlage und den spezifischen Einstellungsproblemen eines Unternehmens ab. Die Ergebnisse zeigen auch, dass die Unternehmen entsprechend den spezifischen Einstellungsproblemen flexibel reagieren. Daraus lässt sich ableiten, dass beide Theorien Anwendung auf dem deutschen Arbeitsmarkt finden.
Keywords: J33; J01; D22; 330; hiring process; vacancy; wage and qualification adjustments; establishment survey